P733 Novelties of COVID-19 vaccination beyond efficacy: Nationwide experiences with trough levels, durability, and disease activity among inflammatory bowel disease patients. (30th January 2023) - Resál, T; Horváth, M; Bacsur, P; Szántó, K; Rutka, M; Bálint, A; Fábián, A; Bor, R; Szepes, Z; Fekete, J; Miheller, P; Molnár, T
Abstract: Background: The SARS-CoV-2 pandemic has raised issues in the management of inflammatory bowel diseases (IBD). This study aimed to assess the efficacy of different anti-SARS-CoV-2 vaccines under different treatments in IBD patients and identify predictive factors associated with lower serological response, including anti-TNF drug levels. Methods: A prospective, multicentre study of IBD patients was conducted following mRNA and non-mRNA anti-SARS-CoV-2 vaccination. Healthy control (HC) patients were enrolled to reduce bias. Baseline and week 14 samples were obtained following the second dose to assess the impact of conventional and biological treatments. Clinical and biochemical activity, serological response level, and anti-TNF drug levels were measured. Results: This study included 199 IBD (Table 1.; mean age, 40.9 ± 12.72 years) and 77 HC participants. Most patients (76.9%) and all HCs received mRNA vaccines. Half of the IBD patients were on biological treatment (Table 2.; anti-TNF 68.7%). Combined immunomodulation and biological treatment were associated with lower serological response (Figure 1.; p<0.001), and mRNA vaccination promoted better antibody levels (p<0.001). Higher adalimumab levels caused lower serological response (p=0.006). W8 persistence of anti-SARS-CoV-2 level was equal in IBD and HC groups (Figure 2.; p>0.05). Vaccination had no impact on disease activity. Conclusion: Anti-SARS-CoV-2 vaccination is considerably efficacious in IBD patients, with mRNA vaccines promoting better antibody levels. The negative impact of combined biological treatment, especially with high adalimumab drug levels, on serological response to vaccination should be considered. Although mid-term durability of vaccination is encouraging, more data are needed to expand existing understanding on this issue.